2004
DOI: 10.1037/0278-6133.23.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Physical Adjustment to Breast Cancer Over 4 Years: Identifying Distinct Trajectories of Change.

Abstract: The goal of this study was to identify distinct trajectories of adjustment to breast cancer over 4 years as well as to distinguish among the different trajectories. The mental and physical functioning of 287 women with breast cancer who remained alive and disease free through 4 years of follow-up were examined. The majority of women showed slight and steady improvement in functioning with time, but subgroups of women were identified who showed marked improvement and marked deteriorations over time. Age success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

63
387
4
22

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(476 citation statements)
references
References 58 publications
63
387
4
22
Order By: Relevance
“…In bivariate tests, they also reported less frequent distress about their family's future and less fatigue. These effects of partner status are conceptually consistent with other evidence that social resources predict better psychological well-being over time (Ganz et al, 2002;Helgeson et al, 2004).…”
Section: Long-term Cancer Survivorssupporting
confidence: 87%
See 2 more Smart Citations
“…In bivariate tests, they also reported less frequent distress about their family's future and less fatigue. These effects of partner status are conceptually consistent with other evidence that social resources predict better psychological well-being over time (Ganz et al, 2002;Helgeson et al, 2004).…”
Section: Long-term Cancer Survivorssupporting
confidence: 87%
“…At the bivariate level, trait optimism related to better long-term well-being on nine of the 12 QLACS scales, and eight of these held up in multivariate tests. It seems very clear that personality is an important contributor to long-term differences in QOL Helgeson et al, 2004), and it would be foolhardy to disregard its contribution.…”
Section: Long-term Cancer Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other cancers [34], levels of anxiety/ depression tended to decrease as time since diagnosis increased. A cancer diagnosis is a traumatic event, and coming to terms with it requires a significant shift in perspective, which could explain these findings.…”
Section: Discussionmentioning
confidence: 69%
“…Previous research has identified several distinct trajectories in physical and psychological functioning from four years after initial diagnosis [53]. Increasing age was associated with lower functioning and deterioration over time.…”
Section: Discussionmentioning
confidence: 89%